Critique and evaluation of published articles quality of Health Sciences qualitative Researches Journal based on CASP scale - Shokooh Varai; Nahid Dehghan Nayeri; Seyedeh Faezeh Hosseiny; Hadi Ahmadi Chenari (Kerman University of Medical Sciences, 2020)
Introduction: Recently, rate of journals and published article in the medical sciences has grown, but the quality of these journals and published articles should be criticized. Therefore, this study was conducted with the aim of criticizing quality of published studies in the qualitative research in health sciences journal based on the CASP scale. Methods: This study has been done with a cross-sectional descriptive method. In this study, the quality assessment of qualitative articles published in the Journal of Qualitative Research in Health Sciences in two steps was performed. In the first stage, the quantity of published studies by descriptive statics has been investigated. In the second stage, based on CASP scale evaluation was perform. Results: The highest percentage of published articles related to content analysis with 52.9% and the lowest percentage of published articles related to ethnography and mixed method with 0.42%. In the 83.1 percentage of published articles, CASP-related indicators are also observed. The highest compliance rate of CASP scale indicators is related to the index of the clarity of the research goals, which is observed in 100% of published articles. The least observance of the indexes in the published articles is related to ethical questions which 65.5 percentage of published articles has been followed. In general Conclusion: Based on findings, recently the quality and quantity of published articles in Qualitative Research in Health Sciences journal is growing, but rate of some types of published studies and their quality is low, which these items should be improved.